Karakteristik dan Kelimpahan Mikroplastik pada Sedimen Ekosistem Terumbu Karang di Perairan Padangbai, Karangasem, Bali - Saragi, Melan Alprino; Hendrawan, I Gede; Giri Putra, I Nyoman (Journal of Marine Research and Technology; Vol 8 No 1 (2025): FEBRUARI 2025DO - 10.24843/JMRT.2025.v08.i01.p10, 2025)
Plastic waste is one of the types of waste we often find in the sea. Plastic waste is a complex decomposing material, but an oxidation process using ultraviolet (UV) light or mechanical processes can cause plastic particles to break down to micro-size. Microplastics are defined as plastic fragments smaller than 5 millimeters. This research aims to discover the characteristics and abundance of microplastics in coral reef ecosystem sediments in the waters of Padangbai Bali in October 2023. Bed load samples were taken at high tide during the transition season II. The purposive sampling method determined the research location (station). There are two station locations. At each station, 10 samples were taken using the purposive sampling method. Preparation for microplastic analysis is carried out in the laboratory in several stages, namely drying, homogenizing, weighing, separating density and WPO, and filtering. Identification of types of microplastics is carried out in the laboratory. Characteristics of microplastic samples were identified based on the type, number, size, and color of microplastics. Then, calculate the abundance. The total number of microplastics found was 173 particles, with the types of microplastics including 95% fiber, 4% fragments, and 1% film, where fiber dominated. The size range of microplastics found was 0.1 - 4.7 mm. The size of the microplastics found was categorized as <0.5, 0.5-1, 1-3, and 3-5 mm, dominated by microplastics measuring 1-3 mm with a total percentage value for both stations of 53%. The colors of the microplastics found were Blue, Brown, Purple, Green, Red, and Orange. Purple is the most common color found, with a percentage value of 40%. The average abundance of microplastics reached 43.3 ± 5.2 particles/kg.